2017
DOI: 10.1038/srep41101
|View full text |Cite
|
Sign up to set email alerts
|

Cortical mechanisms for afterimage formation: evidence from interocular grouping

Abstract: Whether the retinal process alone or retinal and cortical processes jointly determine afterimage (AI) formation has long been debated. Based on the retinal rebound responses, recent work proposes that afterimage signals are exclusively generated in the retina, although later modified by cortical mechanisms. We tested this notion with the method of “indirect proof”. Each eye was presented with a 2-by-2 checkerboard of horizontal and vertical grating patches. Each corresponding patch of the two checkerboards was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…is the process that mediates interocular grouping related to that which generates superimposition? One recent study showed that when decreasing stimulus strength bilaterally for both split-gratings, IOG increases 59 , which we also found when lowering the contrast bilaterally for L and LM gratings ( Fig. 2A).…”
Section: Why Do High-visibility Lm Percepts Not Predominate Over Low-supporting
confidence: 85%
“…is the process that mediates interocular grouping related to that which generates superimposition? One recent study showed that when decreasing stimulus strength bilaterally for both split-gratings, IOG increases 59 , which we also found when lowering the contrast bilaterally for L and LM gratings ( Fig. 2A).…”
Section: Why Do High-visibility Lm Percepts Not Predominate Over Low-supporting
confidence: 85%
“…For instance, distinct proposals that incorporate the idea of multiple levels being involved differ regarding whether different levels would be engaged by different stimuli (Alais & Parker, 2006;Wilson, 2003) or whether a given stimulus would engage several levels at the same time (Tong et al, 2006). Nevertheless, our present results add to a body of studies (Dong, Holm, & Bao, 2017;Holten et al, 2016;Stuit et al, 2011Stuit et al, , 2014 that have separately assessed grouping based on eye-based cues and grouping based on cues that go beyond eye of origin (in these cases, image-based cues) and that all point to monocular information as critical (also see Quinn & Arnold, 2010). Perhaps, then, the multiple levels at which binocular rivalry grouping and, potentially, binocular rivalry competition more generally, can occur, are restricted to areas at which monocular information is available.…”
Section: Discussionmentioning
confidence: 62%
“…Still others, claimed that afterimages occur through adaptation of cortical mechanisms that involve shape and object recognition 19-22,35 , binocular integration 23,24 and/or colour constancy 25 , contradicting classical evidence for a retinal origin 26,27 . Top-down effects on colour perception are well known 36,37 .…”
Section: Discussionmentioning
confidence: 99%